Characterization of Pekmez Samples Produced with Different Fruits According to Sugar, Organic Acid, Antioxidant Activities, and Moisture Contents - Kalaycıoğlu, Zeynep (Igdir University, 2023)
Chemical properties of grape, cranberry, blueberries, pomegranate, black mulberry, juniper, and carob pekmez samples were investigated in this study. Capillary electrophoresis was used to assess the organic acids and sugar levels of pekmez samples. The two main sugars were found to be as glucose and fructose. Juniper pekmez has the lowest sugar with 22.6 g /100 g glucose and 20.1 g /100 g fructose. Black mulberry (35.6 g/100 g) has the highest glucose whereas grape (45.8 g /100 g) includes the highest fructose. Each pekmez samples included 8 organic acids which are oxalic, tartaric, malic, citric, succinic, acetic, lactic, and gluconic acid. 1,1-diphenyl-2-picryl-hydrazil (DPPH) technique was applied for testing the antioxidant activities. Carob pekmez scavenged DPPH the most with 96.28% inhibition value. The other pekmez samples have inhibited DPPH with the values ranging between 58.04% (cranberry) to 90.16 (juniper). The samples' total phenolic levels ranged from 265 mg GAE/g (blueberry) to 1070 mg GAE/g (grape). Moisture contents were measured using a moisture analyzer. Cranberry pekmez (19.06%) and grape pekmez (12.24%) have significantly the highest moisture compared to other samples changing between 2.41% and 5.10%.
Keywords: Glucose; Fructose; Organic acid; DPPH; Total phenolic contents; Chemical Engineering; Kimya Mühendisliği